Resilience as an urban strategy: a comparison of resources and interventions in the European Recovery Plans for the green transition - Gaglione, Federica; Ayiine-Etigo, David Ania (TeMA - Journal of Land Use, Mobility and Environment, 2021)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is a continuous update about emerging topics concerning relationships among urban planning, mobility, and environment, thanks to a collection of short scientific papers written by young researchers. The Review Notes are made up of five parts. Each section examines a specific aspect of the broader information storage within the main interests of the TeMA Journal. In particular: the Town Planning International Rules and Legislation. Section aims at presenting the latest updates in the territorial and urban legislative sphere. The ecological transition is one of the most important missions within the recovery and resilience plans that aim towards an increasingly sustainable city model. The reference scientific literature highlights the importance of studying the relationships between energy policy and the physical-functional organization of urban systems. In this direction, the content of this review aims to define the framework of the interventions and resources in the resilience and recovery plans of two European states of Spain and Ireland. We review their ecological and green revolution/transition reforms in a comparative study to Italy and Germany. The aim is to define the role and impacts of these reforms in future urban strategies.